3D bioprinting mesenchymal stem cell-laden construct with core–shell nanospheres for cartilage tissue engineering. (8th March 2018) - Zhu, Wei; Cui, Haitao; Boualam, Benchaa; Masood, Fahed; Flynn, Erin; Rao, Raj D; Zhang, Zhi-Yong; Zhang, Lijie Grace
Abstract: Cartilage tissue is prone to degradation and has little capacity for self-healing due to its avascularity. Tissue engineering, which provides artificial scaffolds to repair injured tissues, is a novel and promising strategy for cartilage repair. 3D bioprinting offers even greater potential for repairing degenerative tissue by simultaneously integrating living cells, biomaterials, and biological cues to provide a customized scaffold. With regard to cell selection, mesenchymal stem cells (MSCs) hold great capacity for differentiating into a variety of cell types, including chondrocytes, and could therefore be utilized as a cartilage cell source in 3D bioprinting. In the present study, we utilize a tabletop stereolithography-based 3D bioprinter for a novel cell-laden cartilage tissue construct fabrication. Printable resin is composed of 10% gelatin methacrylate (GelMA) base, various concentrations of polyethylene glycol diacrylate (PEGDA), biocompatible photoinitiator, and transforming growth factor beta 1 (TGF- β 1) embedded nanospheres fabricated via a core–shell electrospraying technique. We find that the addition of PEGDA into GelMA hydrogel greatly improves the printing resolution. Compressive testing shows that modulus of the bioprinted scaffolds proportionally increases with the concentrations of PEGDA, while swelling ratio decreases with the increase of PEGDA concentration. Confocal microscopy images illustrate that the cells and nanospheres are evenly distributed throughout the entire bioprinted construct. Cells grown on 5%/10% (PEGDA/GelMA) hydrogel present the highest cell viability and proliferation rate. The TGF- β 1 embedded in nanospheres can keep a sustained release up to 21 d and improve chondrogenic differentiation of encapsulated MSCs. The cell-laden bioprinted cartilage constructs with TGF- β 1-containing nanospheres is a promising strategy for cartilage regeneration.